Enhancing nutrient efficiency through optimizing protein levels in lambs: Involvement of gastrointestinal microbiota - Zhibin Luo; Huimin Ou; Christopher S. McSweeney; Zhiliang Tan; Jinzhen Jiao (Animal Nutrition)
Improving the nutrient utilization efficiency of ruminants is of utmost significance for both economic and environmental benefits. Optimizing dietary protein levels represents a key nutritional strategy to enhance ruminant growth performance and reduce nitrogen emissions. In a 63-day experiment, 24 healthy Hulunbuir lambs (initial weight 17.1 ± 2.0 kg, 2.5 months old) were subjected to three treatments: a low-protein diet (LP; crude protein of 78.4 g/kg dry matter [DM]), a medium-protein diet (MP; crude protein of 112.0 g/kg DM), and a high-protein diet (HP; crude protein of 145.6 g/kg DM), with 8 lambs in each treatment (4 males and 4 females). Lambs in the MP treatment presented greater daily weight gain and feed conversion ratio than those in the HP treatment (P < 0.05, quadratically). Compared with the LP treatment, the MP treatment resulted in greater crude protein digestibility (P < 0.001, quadratically) and acid detergent fiber digestibility (P = 0.022, quadratically). In the serum, the urea nitrogen level increased quadratically with increasing dietary protein levels (P < 0.001), while the LP treatment exerted the highest concentrations of glutamate, glycine, alanine, and histidine (P < 0.05, quadratically). The ammonia nitrogen concentrations in the rumen and colon increased quadratically with increase in dietary protein levels (P < 0.05). The HP treatment increased the molar concentrations of isobutyrate and isovalerate in the rumen and colon (P < 0.05, quadratically). In contrast, the LP treatment decreased the molar proportion of acetate (P = 0.007, quadratically) and increased the molar proportion of butyrate (P < 0.001, quadratically) in the colon. The microbial diversity and structure were significantly altered by dietary protein level intervention across all gastrointestinal regions. The rumen of the MP treatment was enriched with fiber-degrading bacteria Fibrobacter_succeinogenes and starch-degrading bacteria Selenomonas_ruminantium. The colon in the LP treatment harbored microbial biomarkers including Escherichia spp. and Lactobacillus amylovorus, and the colon in the MP treatment was characterized by the enrichment of Solibacillus_cecembensis. These findings suggest that the MP diet with a crude protein content of 112.0 g/kg DM improved the growth performance and nutrient efficiency of lambs, which was achieved via the involvement of the gastrointestinal microbiota.